The Baluch question in Pakistan and the right of self-determination - Baloch, Inayat Allah (Pakistan in its fourth decade, 1983)
Geschichte des Belutschistanproblems seit dem 14. Jh. unter besonderer Berücksichtigung des Kampfes um Selbstbestimmung in Pakistan. (DÜI-Hns)
Lit.Hinw
Keywords: Pakistan